1988
DOI: 10.1007/bf00002933
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of some Venezuelan blackwater rivers based upon physico-chemical properties of their humic substances

Abstract: Abstract. The dissolved humic substances of seven Venezuelan blackwater rivers, belonging to different tropical biogeographical regions, were analyzed. Fractionation using Sephadex gel together with an analysis of their fluorescence, absorbance and infrared spectral properties, showed differences between their humic substances. These differences were related to their biological sources and humification environment. Statistical analysis of the properties of these humic substances allowed us to separate the rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our study also revealed that, for other fish species, the gradient of environmental conditions along the course of the Casiquiare constitutes an ecological barrier for dispersal. The river’s longitudinal fluvial gradient transitions between clearwater conditions having upland hydrological influences, and blackwater conditions associated with the drainage of the sandy, oligotrophic alluvial plains of the Cuchivero geological province (Vegas‐Vilarrúbia et al. , 1988; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed that, for other fish species, the gradient of environmental conditions along the course of the Casiquiare constitutes an ecological barrier for dispersal. The river’s longitudinal fluvial gradient transitions between clearwater conditions having upland hydrological influences, and blackwater conditions associated with the drainage of the sandy, oligotrophic alluvial plains of the Cuchivero geological province (Vegas‐Vilarrúbia et al. , 1988; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pH value (7.08) of Lake Kenyir is typical of bicarbonate-type waters, in which the CO 2 -HCO 3 -CO 3 equilibrium system operates (Payne 1986). Low alkalinity and pH values are indicators of low mineralization and high humic substances (Vegas-Villarubia et al 1988). Being in the main basin of Lake Kenyir, the dam sampling site (site 1) has less opportunity for mineralization to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pH value (7.08) of Lake Kenyir is typical of bicarbonate‐type waters, in which the CO 2 ‐HCO 3 ‐CO 3 equilibrium system operates (Payne 1986). Low alkalinity and pH values are indicators of low mineralization and high humic substances (Vegas‐Villarubia et al . 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The two swamp rivers in our study, however, are natural and undisturbed, with >95% swamp vegetation. They are typical blackwater rivers with low pH, low DO, and variable concentrations of nutrients (Vegas-Vilarrúbia et al, 1988;Küchler et al, 2000;Alkhatib et al, 2007;Horbe and Santos, 2009;Rixen et al, 2010;Ríos-Villamizar et al, 2014). The two focal swamp rivers likely align with "slightly contaminated" NRMN sites because they have DO concentrations approaching hypoxia.…”
Section: Coastal Peat Swamp Riversmentioning
confidence: 99%